Augmented Reality-Based Assemblr Edu Media on Students' Critical Thinking Skills in Civics Subjects for Grade IV at UPT SDN 060874 Medan Perjuangan - Riri Mayuni (Berpusi Publishing, 2026)
This study aims to determine the effect of augmented reality- based assemblr edu learning media on students' critical thinking skills in Civics subjects on the meaning of Pancasila principles in grade IV of UPT SDN 060874 Medan Perjuangan. The method used is a quasi-experimental with a pretest-posttest control group design. The study population was all fourth-grade students, with a sample of two classes, namely class IV A as an experimental class totaling 23 students and class IV B as a control class totaling 21 students. The research instrument was a validated critical thinking ability essay test. The results of the study showed a significant effect of the use of augmented reality-based assemblr edu media on students' critical thinking skills. This can be seen from the average posttest score of the experimental class of 79.57, higher than the control class of 55.33. In addition, as many as 96% of students in the experimental class had achieved the KKM, while the control class had not achieved optimal completion. Thus, it can be concluded that the augmented reality-based assemblr edu learning media is effective in improving students' critical thinking skills and creating more interactive and interesting learning.